2019
DOI: 10.5080/u23274
|View full text |Cite
|
Sign up to set email alerts
|

The Standardization of the Pathological Narcissism Inventory in the Turkish Language and Testing Its Validity and Reliability

Abstract: Psikolojik bir yapı olarak önemine rağmen, narsisizmin tanımlanması ve ölçümü farklı çalışmalarda tutarsızlık göstermektedir. Patolojik narsisizmin yapısının tanımlanmasındaki aşırı sınırlılık ve ölçümünün yetersizliği, Pincus ve arkadaşları (2009) tarafından Patolojik Narsisizm Envanterini (PNE) geliştirilmesinde etken olmuştur. Narsistik büyüklenmecilik ve kırılganlığın hem açık hem de örtük ifadelerini değerlendiren yapısıyla bu ölçüm aracı, patolojik narsisizm çok boyutlu ölçülmesine olanak tanımaktadır. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Pathological Narcissism Inventory (PNI) was developed by Pincus et al ( 2009 ), while the Turkish adaptation studies were carried out by Sen and Barişkin ( 2019 ). The scale is of the 6-point Likert-type comprising 52 items.…”
Section: Methodsmentioning
confidence: 99%
“…Pathological Narcissism Inventory (PNI) was developed by Pincus et al ( 2009 ), while the Turkish adaptation studies were carried out by Sen and Barişkin ( 2019 ). The scale is of the 6-point Likert-type comprising 52 items.…”
Section: Methodsmentioning
confidence: 99%
“…Pathological Narcissism Inventory (PNI): It is a 6-point Likert-type (ranging from 0: “not at all like me” to 5: “very much like me”) measurement scale consisting of 52 items that examine the vulnerable and grandiose dimensions of narcissism (Pincus et al, 2009). Şen and Barışkın (2019) adapted the scale to Turkish, revealing a factor structure comprising two dimensions (grandiose and vulnerable) and five sub-dimensions. Accordingly, in the PNI, the “Grandiose Self” (GS) and the “Grandiose Fantasy” (GF) (with negative loading) factors represent the grandiosity dimension of narcissism while the factors of “Recognition Expectations” (REX), “Vulnerable Self” (VS), “Approval Seeking” (AS), and “Self Sacrificing” (SS) represent the vulnerability dimension of narcissism.…”
Section: Methodsmentioning
confidence: 99%
“…It was created by Pincus et al (2009), and it was translated into Turkish by Şen and Barışkın (2019). There are 52 items on the 6-point Likert scale.…”
Section: Pathological Narcissism Inventory (Pni)mentioning
confidence: 99%
“…The most common measurement scale is the Pathological Narcissism, the Pathological Narcissism Inventory (PNI), narcissism with two upper factors (grandiose narcissism, vulnerable narcissism) and 7 sub-factors (Pincus et al, 2009). Psychometric studies on PNI translated into many languages showed that correlations of discriminant validity combined with similar measurement tools are high (Besser & Zeigler-Hill, 2011;Fossati et al, 2015;Morf et al, 2017;Şen & Barışkın, 2019;Thomas et al, 2012;You et al, 2013). It has been proposed that the PNI is suitable for assessing healthy narcissism and clinical cases and that an increase in the total score points vulnerable narcissism (Pincus, 2013;Thomas et al, 2012).…”
mentioning
confidence: 99%